Rafael Dieste and Sebastián Martínez-Risco: Buenos Aires and the Galician Academy - Freixeiro Mato, Xosé Ramón (Madrygal. Revista de Estudios Gallegos, 2016)
Although the Spanish Civil War (1936-39) interrupted the recovery of Galician cultural identity, this process was continued by emigrants. The writer Rafael Dieste is an example of an intellectual who pioneered Galician culture in Buenos Aires for two decades after the war. During that time, Sebastián Martínez-Risco also travelled there with the aim of keeping the spirit of galicianism alive and to gain support for the Galician Academy.